Measuring patient experience: a systematic review to evaluate psychometric properties of patient reported experience measures (PREMs) for emergency care service provision - Male, Leanne (Int J Qual Health Care, 2017)
PURPOSE: Knowledge about patient experience within emergency departments (EDs) allows services to develop and improve in line with patient needs. There is no standardized instrument to measure patient experience. The aim of this study is to identify patient reported experience measures (PREMs) for EDs, examine the rigour by which they were developed and their psychometric properties when judged against standard criteria. DATA SOURCES: Medline, Scopus, CINAHL, PsycINFO, PubMed and Web of Science were searched from inception to May 2015. STUDY SELECTION: Studies were identified using specific search terms and inclusion criteria. A total of eight articles, reporting on four PREMs, were included. DATA EXTRACTION: Data on the development and performance of the four PREMs were extracted from the articles. The measures were critiqued according to quality criteria previously described by Pesudovs K, Burr JM, Harley C, et al. (The development, assessment, and selection of questionnaires. Optom Vis Sci 2007;84:663–74.). RESULTS: There was significant variation in the quality of development and reporting of psychometric properties. For all four PREMs, initial development work included the ascertainment of patient experiences using qualitative interviews. However, instrument performance was poorly assessed. Validity and reliability were measured in some studies; however responsiveness, an important aspect on survey development, was not measured in any of the included studies. CONCLUSION: PREMS currently available for use in the ED have uncertain validity, reliability and responsiveness. Further validation work is required to assess their acceptability to patients and their usefulness in clinical practice.